External Ophthalmomyiasis which was Caused by Sheep Botfly (Oestrus ovis) Larva: A Report of 10 Cases - Sucilathangam G.; Meenakshisundaram A.; Hariramasubramanian S.; Anandhi D.; Palaniappan N.; Anna T. (Journal of Clinical and Diagnostic Research, 2013)
Myiasis is the infestation of the tissues and organs of animals or man by fly larvae. Ophthalmic myiasis has been reported from various world regions. In this study, we are presenting the clinical manifestations of external ophthalmomyiasis which was caused by the larvae of the sheep nasal botfly, Oestrus ovis, in 10 patients in the Tirunelveli and the Tuticorin districts of Tamil Nadu state India. All the patients were farmers, who worked in close contact with sheep and goats. All the patients presented with severe conjunctivitis. The larvae were observed in the bulbar conjunctiva and following their removal, the symptom of eye inflammation improved in a few hours.